2015
DOI: 10.1177/2319510x15588383
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Assessment of Hospital Information Systems: A Study of Hospitals in Jalandhar

Abstract: There is a progressive integration of technology by different sectors of our economy so as to enhance the productivity and efficiency of the business operations. However, in the Indian health care sector, it is discouraging to observe that not much is being spent on the hospital information systems (HIS). Technology integration has the potential to not only accelerate the speed but also enhance the quality and efficiency of hospital operations. The present research aims to determine the degree of adoption of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Finally, Table 14 indicated that "being a newly established academic unit" and "inadequacies in numbers of academic and administrative staff" were the most critical factors behind the behavior of not performing quality efforts. These findings seem to be consistent with literature that has focussed on the antecedents of the spread of (Kimberly and Evanisco, 1981), and organizational size (Batra and Pall, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Finally, Table 14 indicated that "being a newly established academic unit" and "inadequacies in numbers of academic and administrative staff" were the most critical factors behind the behavior of not performing quality efforts. These findings seem to be consistent with literature that has focussed on the antecedents of the spread of (Kimberly and Evanisco, 1981), and organizational size (Batra and Pall, 2015).…”
Section: Discussionsupporting
confidence: 91%